Studying peculiarities of cathodic iron reduction from electrolytes based on Fe (III) - Ермоленко, Ирина Юрьевна (Technology audit and production reserves, 2014)
The results of the voltammetric studies of the cathodic reduction of iron from electrolytes based on Fe3+ are analyzed in the paper. It is shown that the simultaneous discharge of Fe3+, FeOH2+ and FeO+ ions occurs under cathodic polarization. The concentration ratio of the electrode active particles in the solution, as well as the pH of the electrolyte, is determined by the initial concentration of Fe3+ ions and the degree of hydrolysis. Characteristic parameters of the electrochemical reaction, namely the Semerano criterion XS = 0,5 and the concentration criterion Xс = 1 indicates irreversibility of the cathode process. Using the algorithm of analyzing the polarization dependency, the staging and mechanism of the process is set. It is shown that the electrochemical reaction of reducing iron (III) is limited by the charge transfer stage and is determined by the adsorption of FeOH2 + ions on the electrode surface and the stage of FeOH+ ionsdissociation. These results serve as a theoretical basis for the development of a stable electrolyte based on iron (III) to form electrolytic coatings with iron alloys.